Exploring physical properties of minimally deformed strange star model and constraints on maximum mass limit in f(𝒬) gravity. Issue 10 (1st October 2022) - Maurya, S.K.; Mustafa, G.; Govender, M.; Newton Singh, Ksh.
Abstract: Our current investigation is inherently linked to the observations of gravitational waves from the GW190814 event which suggests that the source of the signals can be ascribed to a compact binary coalescence of a 22.2 to 24.3 M ⊙ black hole and a compact object endowed with a mass of 2.50 to 2.67 M ⊙ . In the current exposition, we are concerned with modeling of the lower mass component of the coalescence pair. We utilize the f (𝒬) gravity together with the Minimal Geometric Deformation (MGD) technique to obtain compact stellar objects with masses aligned with the GW190814 event. Starting off with the Tolman IV ansatz for one of the metric functions, together with an MIT Bag model equation of state we are able to reduce the problem of fully describing the gravitational behavior of the seed solution to a quadrature. Through the MGD technique, we introduce anisotropy by deforming the radial part of the gravitational potential. This enables us to obtain two new classes of solutions which depend on the metricity parameter, 𝒬 and the deformation constant, β . We show that these two parameters play a crucial role in determining the thermodynamical behavior and stability of our models. In particular, we show that the interplay between the metricity parameter and the deformation constant predicts the mass of the progenitor articulating as the secondary component of GW190814.